Biofortified pearl millet cultivars offer potential solution to tackle malnutrition in India - Govindaraj, Mahalingam; Virk, Parminder K.; Kannati, Anand; Cherian, Binu; Rai, K. N.; Anderson, Meike S.; Pfeiffer, Wolfgang H. (CAB International, 2020)
Dietary deficiency of micronutrients (iron, zinc, vitamin A), leading to micronutrient malnutrition or hiden hunger, has been recognized as a widespread food-related health problem, affecting more than 2 billion people worldwide (White and Broadley, 2009; Stein 2010; fao,2015; Darnton-Hill and Mkparu, 2015). This is primarily attributable to lack of affordability and access to diversified diet, such as fruits, vegetables and livestock products. As a consequence, women, children and infants, belonging to the poorer section of society are malnourished. In particular, deficiencies of iron and zinc are widespread, leading to numerous adverse health consequences , as they play a vital role in various physiological body functions.